Analysis on The Effect of Channel Bandwidth Occupying in LTE Frequency Band on Throughput - Yusnita, Sri; -, Yustini; Markis, Lince; Tristianti, Widia; Wijaya, Taruma Leo (SOTVI, 2023)
The maximum channel capacity of a 4G LTE network will be directly correlated to the channel bandwidth that occupies a certain radio frequency on that network. The number of Resource Blocks (RB), subcarriers, and Resource Elements (RE) as channel resources available to serve users concurrently will depend on the bandwidth channel sizes. Mobile service providers in Indonesia provide scalable channel bandwidth LTE 4G networks on a variety of frequency bands, including adjacent and non-adjacent bands. In this study, it was examined how to channel bandwidth, which changes at 10MHz, 15MHz, and 20MHz, affects throughput to give user equipment the best possible performance (UE). This study makes use of actual measurement data from installed and active eNodeB or cells obtained via the drive test approach. According to the test, each channel's maximum throughput varies, however, there is no linear relationship found between channel bandwidth expansion and throughput. The 20MHz channel bandwidth, which is located in the 2300MHz frequency band, has a maximum throughput value of 64666.80 kbps.